Consequences of Natural and Man-made Disasters on Pregnancy Outcomes and Complications: A Systematic Review - Pashaei Asl , Yousef; Ghanbari-Homaie , Solmaz; Partash , Nasim; Pakzad, Alireza; Faridaalaee, Gholamreza (Archives of Academic Emergency Medicine, 2024)
Introduction: Due to their unique circumstances, pregnant women face a heightened risk of experiencing pregnancy complications during and after catastrophic events. This study aims to investigate the consequences of both natural and man-made disasters on pregnancy outcomes. Method: This study is a systematic review. Searches were performed until May 31, 2024, in the electronic databases including Medline, Web of Science, Embase, and Scopus. Outcomes such as preterm birth, low birth weight (LBW), small for gestational age (SGA), stillbirth, spontaneous abortion, and pregnancy-related blood pressure complications were studied. Result: The search conducted in the databases yielded 3307 non-duplicate records. After reading the abstracts, 3204 articles were excluded based on inclusion and exclusion criteria. Full texts of 103 article were obtained. However, upon reading the full texts of articles, 13 of them did not meet the inclusion criteria for the study. Consequently, 90 articles were ultimately included. Conclusion: Natural and man-made disasters exert significant influence on adverse pregnancy outcomes. While it is impossible to prevent the incidence of natural disasters and often man-made disasters occur abruptly, the negative consequences of disasters, particularly natural ones, can be mitigated by enhancing prenatal care and avoiding detrimental elements such as smoking and alcohol.